Fragmented DNA and apoptotic bodies document the programmed way of cell death in hybridoma cultures - Franĕk, F; Vomastek, T; Dolníková, J (Cytotechnology, 1992)
Markers of apoptosis were followed in batch hybridoma cultures carried out in protein-free medium. Samples were collected on day 0, representing early exponential phase (viability 91%), and on day 8, corresponding to late stationary phase (viability 8%). The apoptotic index reflecting the relative number of bodies insoluble in 6 M guanidinium hydrochloride in the culture of day 8 (30%) exceeded markedly the index in the culture of day 0 (2.5%). A gel chromatography on Sepharose 2B was developed for quantitative evaluation of fragmented cellular DNA. This analysis, including a correction for nonspecific fragmentation, showed that on day 8 more than 30% of cellular DNA was fragmented, whereas on day 0 it was less than 5%. Control necrotic cells prepared by rapid killing in 1% sodium azide displayed a low apoptotic index (2.4%) and low DNA fragmentation. Electrophoretic patterns in agarose gel showed a typical "ladder" of fragments in the DNA sample of day 8. The demonstration of fragmented cellular DNA and of the high incidence of apoptotic bodies at late stationary phase adds substantial weight to the view that in hybridoma cultures apoptosis represents the prevalent mode of cell death.
Keywords: poškození DNA; Animals; DNA Damage; nekróza; Cell Line; Hybridomas; Apoptosis; hybridomy; Mice; buněčné linie; gelová chromatografie; Necrosis; apoptóza; myši; Chromatography, Gel; zvířata